1994
DOI: 10.1084/jem.179.4.1361
|View full text |Cite
|
Sign up to set email alerts
|

Impaired interleukin 12 production in human immunodeficiency virus-infected patients.

Abstract: Peripheral blood mononuclear cells (PBMC) from human immunodeficiency virus (HIV)-infected patients, asymptomatic or with acquired immunodeficiency virus, produced 10-fold less interleukin 12 (IL-12) free heavy chain and fivefold less biologically active IL-12 heterodimer than PBMC from uninfected healthy donors when challenged in vitro with the common human pathogen Staphylococcus aureus. In contrast, PBMC from HIV-infected individuals and uninfected control donors produced similar levels of tumor necrosis fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
201
3

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 414 publications
(217 citation statements)
references
References 23 publications
13
201
3
Order By: Relevance
“…9 The reason for this change in the cytokine profile is due to impaired production of IL-12 (a potent Th1 inducer). 10 On the other hand, susceptibility or resistance to L. infantum infection has also been demonstrated to be regulated by the two different Th lymphocyte subsets. 11 The most potent cytokine for the induction of leishmanicidal activity in macrophages is IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…9 The reason for this change in the cytokine profile is due to impaired production of IL-12 (a potent Th1 inducer). 10 On the other hand, susceptibility or resistance to L. infantum infection has also been demonstrated to be regulated by the two different Th lymphocyte subsets. 11 The most potent cytokine for the induction of leishmanicidal activity in macrophages is IFN-␥.…”
Section: Discussionmentioning
confidence: 99%
“…killing is indeed delayed (Melby, 1991). Inhibition of MP IL-12 production and resulting Th1 responses is not unique to Leishmania; viruses (Chehimi et al, 1994;Chougnet et al, 1996;Karp et 1996) and bacteria (Marth and Kelsall, 1997;Sutterwala et al, 1997;Matsunaga et al, 2003) also exploit this mechanism to avoid clearance.…”
Section: Introductionmentioning
confidence: 99%
“…killing is indeed delayed (Melby, 1991). Inhibition of MP IL-12 production and resulting Th1 responses is not unique to Leishmania; viruses (Chehimi et al, 1994;Chougnet et al, 1996;Karp et 1996) and bacteria (Marth and Kelsall, 1997;Sutterwala et al, 1997;Matsunaga et al, 2003) also exploit this mechanism to avoid clearance.The general nature of impaired IL-12 production in Leishmania spp.-infected MP has extended to every IL-12 agonist that has been tested. Leishmania spp.-infected MP are unable to produce IL-12 even in response to strong inflammatory stimuli, including microbial stimuli, e.g., lipopolysaccharide (LPS), Staphylococcus aureus (SAC), Toxoplasma gondii antigen, and mycobacteria (Carrera et al, 1996;Sartori et al, 1997;Belkaid et al, 1998;Weinheber et al, 1998;Piedrafita et al, 1999), and T-cell-dependent agonists, e.g., IFN-γ and CD40L (Carrera et al, 1996;Belkaid et al, 1998;Weinheber et al, 1998;Piedrafita et al, 1999).…”
mentioning
confidence: 99%
“…Other studies have demonstrated that HIV-1 not only impairs the function of DC [35] (H Donaghy pers commun.) but also that HIV-1 can inhibit IL-12 secretion from these cells [36,37]. HIV-1 and HCV co-infection may therefore be expected to significantly impair function precluding the use of this 'easy-to-generate' immune cell subset in immunotherapeutic approaches.…”
Section: Introductionmentioning
confidence: 99%